2017
DOI: 10.1590/1806-93042017000200007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the mothers' nutritional status with that of a child population from São Tomé Principe, "Africa"

Abstract: Objectives: analyse the relation between the nutritional status of children with 0 to 60 months in São Tome and Principe (STP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Selain itu, faktor resiko yang berhubungan dengan stunting adalah tidak terdapat hubungan yang signifikan antara tingkat pengetahuan ibu tentang gizi dengan kejadian stunting (16). Hal ini disebabkan oleh tumbuh kembang anak dipengaruhi oleh faktor-faktor keluarga lainnya, seperti: pekerjaan/ pendapatan keluarga, pendidikan orang tua, stabilitas rumah tangga, dan kepribadian orang tua (17)(18)(19).…”
Section: Hubungan Karakteristik Keluarga Dengan Kejadian Stuntingunclassified
“…Selain itu, faktor resiko yang berhubungan dengan stunting adalah tidak terdapat hubungan yang signifikan antara tingkat pengetahuan ibu tentang gizi dengan kejadian stunting (16). Hal ini disebabkan oleh tumbuh kembang anak dipengaruhi oleh faktor-faktor keluarga lainnya, seperti: pekerjaan/ pendapatan keluarga, pendidikan orang tua, stabilitas rumah tangga, dan kepribadian orang tua (17)(18)(19).…”
Section: Hubungan Karakteristik Keluarga Dengan Kejadian Stuntingunclassified
“…Previous studies in Ethiopia and other parts of the world showed that maternal nutritional status and feeding practices are associated with growth indices of their children [4,5,6,7,8]. A more recent study by Desalegn and colleagues showed that maternal Body Mass Index (BMI) and dietary pattern of lactating mothers were negatively affected by maternal fasting status, and during Ethiopian Orthodox lent fasting period regardless of fasting status in rural Ethiopia [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, Temesgen et al showed that women from high-income families were 75% less likely to be underweight (Temesgen et al, 2015). A crosssectional study from Brazil showed that homemaker's women were those presented both low food purchasing capacity and poor nutritional status (low mean BMI) (Silva et al, 2017). This may be important for mothers to have their own money so that they can buy a variety of food, especially ASFs, thereby improving diet diversity and nutrition outcomes.…”
Section: Discussionmentioning
confidence: 99%